Dynamic mechanochemical feedback between curved membranes and BAR protein self-organization - Anabel-Lise Le Roux (Nature Portfolio, 2021)
Amphiphysin BAR proteins reshape membranes, but the dynamics of the process remained unexplored. Here, the authors show through experiment and modelling that reshaping depends on the initial template shape, occurs even at low initial curvature, and involves the coexistence of isotropic and nematic states.